Caffeic acid phenethyl ester guards against benign prostate hypertrophy in rats: Role of IGF‐1R/protein kinase‐B (Akt)/β‐catenin signaling. Issue 6 (30th March 2018) - Omar, Hany A.; Tolba, Mai F.
Abstract: Benign prostate hypertrophy (BPH) is among the most common diseases with a huge impact on the quality of life of elderly men. There is a current need for the development of well‐tolerated and effective preventive strategies to improve the clinical outcome. Caffeic acid phenethyl ester (CAPE) is an important active ingredient isolated from honey‐bee propolis with potent anti‐proliferative, anti‐inflammatory and antioxidant effects. These properties promote CAPE as a promising candidate to be tested as an alternative therapy for BPH, which is still uninvestigated. Herein, we tested the ability of CAPE to guard against testosterone‐induced BPH and investigated the involvement of IGF1‐R/Akt/β‐catenin signaling as a protective mechanism in testosterone‐induced BPH rat model. Treatment with CAPE reduced testosterone‐induced increase in the prostate index and histopathological alterations. In addition, co‐treatment with CAPE significantly suppressed insulin‐like growth factor‐1 receptor (IGF‐1R)/Akt/β‐catenin/cyclinD1 axis as well as tumor necrosis factor‐α level and nuclear factor (NF)‐kB activity. Furthermore, the treatment with CAPE replenished the antioxidant defense systems, superoxide dismutase (SOD) and reduced glutathione (GSH) with subsequent reduction in prostate tissue lipid peroxides. This study highlights the potential merit of CAPE‐enriched propolis formulations to protect elderly men against the development of BPH. © 2018 IUBMB Life, 70(6):519–528, 2018